Country Music USA: 50th Anniversary Edition - Bill C. Malone , Tracey E. W. Laird (University of Texas Press, 2018)
Since its first publication in 1968, Bill C. Malone’s Country Music USA has won universal acclaim as the definitive history of American country music. Starting with the music’s folk roots in the rural South, it traces country music from the early days of radio into the twenty-first century. In this fiftieth-anniversary edition, Malone, the featured historian in Ken Burns’s 2019 documentary on country music, has revised every chapter to offer new information and fresh insights. Coauthor Tracey Laird tracks developments in country music in the new millennium, exploring the relationship between the current music scene and the traditions from which it emerged.